Contribution Of Limb Length And Brick Flexibility to Smash Ability In Volley Balls Lueng IE Aceh Big White Elang - Syamsulrizal Syamsulrizal; Muhammad Iqbal; Zahara Zahara (Inspiree)
The  purpose  of  the study. This study aims to study and find out this method is used to obtain information directly from informants regarding "The Contribution of Leg Length and Flexibility of Togok To The Ability Of Volleyball Smash At The White Eagle Club Lueng Ie Aceh Besar 2021.